Job Aid for Faculty Development: PBL Process - Christopher Reznich (Association of American Medical Colleges, 2007)
Abstract This job aid is a two-sided pocket card designed to help users recall the stages of the problem-based learning (PBL) small group process and identify the preceptor behaviors that help further educational goals. One side of the card contains a brief, step-by-step description of the PBL discussion process. The other contains the goals for the second-year Michigan State University College of Human Medicine curriculum and PBL preceptor behaviors that help to achieve those goals. Users will want to substitute their own institution's goals and preceptor behaviors. This resource has been used to train over 100 PBL preceptors at the authors' institution. Users have expressed a preference for the real pocket-sized card to the lab coat-sized card.